Opportunities and Challenges of Optimized Method of Teaching Using Virtual Classroom Instructional Technology During Covid-19 Pandemic in Public Secondary Schools in Nigeria - Yunisa, A. Y.; Yunisa, B. (Kashere Journal of Education, 2021)
This study examined the opportunities and challenges of optimized method of teaching using virtual classroom technology during COVID-19 pandemic in Nigerian public schools. The study adopted a descriptive survey research design. The population of the study is 9789 students and 3251 teachers. The samples were drawn using random sampling technique in selecting fifty-six (56) teachers and one hundred and thirty-seven students (137) within North central geo-political zone in Nigeria. Data was collected using a validated questionnaire for teachers. The instruments were validated by experts. The instrument contained affirmation questions to ascertain the validity of the response of teachers on instructional technology with a reliability coefficient of 0.68. Two research questions were formulated to guide the study. Chi square was used to analyze the data for the research questions and tested at 0.05 level of significance using statistical package for social sciences (SPSS) Version 25. The findings revealed teachers did not utilize virtual classroom technology and that they were faced with a number of challenges which include but not limited to lack of expertise in the use of these gadgets, lack of stable power supply, inadequate finance to purchase etcetera. The study recommended that school administrators should collaborate with various stockholders to put all virtual classroom infrastructure in place to encourage teachers to employ virtual classroom technology when needed, School principals should collaboration with various stakeholders in organizing training and symposium for teachers on the use of virtual classroom technology.